Answer:
(-5, 3)
Step-by-step explanation:
B = 2M - A
B = 2(-2, 5) -(1, 7) = (-4-1, 10-7) = (-5, 3)
27 times 6
27*6=162
Julia made $162 that morning
I think that’s right
Answer:
Because each of the two numbers is a factor of the product, and since the
product has at least those two factors, it's a composite number by definition.
Step-by-step explanation:
can i have brainliest please and thxs
<h3>
Answer:</h3>
- y = -(x -3)² +3 . . . . (agrees with your answer)
- see the attachment for a graph
<h3>
Step-by-step explanation:</h3>
Factoring the leading -1 from the first two terms, we have ...
... y = -(x² -6x) -6
Adding 9 inside parentheses to complete the square, then adding the opposite amount outside parentheses, we have ...
... y = -(x² -6x +9) -6 +9
... y = -(x -3)² +3
Answer:
48 is the answer
Step-by-step explanation: